2012
DOI: 10.1186/1471-2229-12-109
|View full text |Cite
|
Sign up to set email alerts
|

Improved efficiency of doubled haploid generation in hexaploid triticale by in vitro chromosome doubling

Abstract: BackgroundDoubled haploid production is a key technology in triticale research and breeding. A critical component of this method depends on chromosome doubling, which is traditionally achieved by in vivo treatment of seedlings with colchicine.ResultsIn this study we investigated the applicability of an in vitro approach for chromosome doubling based on microspore culture. Our results show a pronounced increase in the proportion of doubled haploid triticale plants compared to the spontaneous doubling rate, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…Acquiring embryogenic competence requires the application of some type of external cue(s) leading to a stress(s) that preventing microspores from continuing their normal mode of gametophytic development and inducing sporophytic differentiation. In the genus Brassica, microspores are often induced by heat shock (Prem et al 2005), anti-microtubular (Würschum et al 2012), and mutagenic agents (Ahmadi et al 2012), stress hormones (Ahmadi et al 2014a) or polyamines (Ahmadi et al 2014b). Upon stress treatment and embryogenesis induction, many biochemical and morphological changes occur which is closely related to alterations in gene expression pattern (Tsuwamoto et al 2007;Muñoz-Amatriaín et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Acquiring embryogenic competence requires the application of some type of external cue(s) leading to a stress(s) that preventing microspores from continuing their normal mode of gametophytic development and inducing sporophytic differentiation. In the genus Brassica, microspores are often induced by heat shock (Prem et al 2005), anti-microtubular (Würschum et al 2012), and mutagenic agents (Ahmadi et al 2012), stress hormones (Ahmadi et al 2014a) or polyamines (Ahmadi et al 2014b). Upon stress treatment and embryogenesis induction, many biochemical and morphological changes occur which is closely related to alterations in gene expression pattern (Tsuwamoto et al 2007;Muñoz-Amatriaín et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…and rye (Secale cereale L.) developed to combine grain quality, productivity, and disease resistance of wheat with rye's excellent environmental adaptability and tolerance. It is amenable to androgenesis (Immonen and Robinson 2000;Oleszczuk et al 2004;Ponitka and Slusarkiewicz-Jarzina 2007;Würschum et al 2012) and registered cultivars have been created via the doubled haploid approach (Dr. Z. Banaszak-Plant Breeding Danko Ltd Poland, Dr. H. Wos-Plant Breeding Strzelce Ltd Poland, pers. comm.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro application of colchicine is an alternative for doubled haploid production using microspore culture. Using this method of colchicine application, Würschum et al (2012) showed a pronounce increase in the proportion of doubled haploid triticale plants, thus a promising alternative to the in vivo approach. The antimicrotubule herbicides such as amiprophos methyl, oryzalin, and pronamide are effective in doubling chromosome sets of maize; being less toxic than that of colchicine (Häntzschel and Weber, 2010).…”
Section: Conventional Methods To Induce Doubled Haploidsmentioning
confidence: 96%